Preparation method of high-modulus, high-strength and high-toughness layered microstructure aluminum-based composite material

Through in-situ self-generating method and alternating jet deposition technology, the aluminum-based composite material with layered microstructure is formed, combined with thermal isostatic pressure and plastic deformation process, the problem of aluminum alloy materials being difficult to improve toughness while improving elastic modulus and strength is solved, and the high-mode, high strength and high toughness performance of the material is achieved.

CN119870474APending Publication Date: 2025-04-25SHANGHAI JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510093180.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

While the existing aluminum alloy materials increase the elastic modulus and strength, it is difficult to simultaneously improve toughness, and the uneven distribution of ceramic particles leads to a decrease in the plasticity of the material.

Method used

In situ self-generating method is used to prepare particle-reinforced aluminum-based composite materials, and a layered microstructure is formed through alternating jet deposition technology, combining thermal isostatic pressure, annealing, plastic deformation and heat treatment processes to achieve non-uniform ceramic particle distribution and non-uniform grain size distribution.

Benefits of technology

The synchronous improvement of elastic modulus, strength and elongation of aluminum alloy materials is achieved, and the overall strong plasticity performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119870474A_ABST
    Figure CN119870474A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-modulus, high-strength and high-toughness layered microstructure aluminum-based composite material, and belongs to the technical field of aluminum alloy materials. The in-situ synthesis particle reinforced aluminum-based composite material and alloy components are subjected to layered microstructure distribution design, ingot casting preparation, hot isostatic pressing, plastic deformation, solution treatment and aging treatment, and the high-modulus, high-strength and high-toughness aluminum-based composite material is obtained through layered heterostructure aluminum-based composite material microstructure design. The preparation and processing method of the aluminum-based composite material provided by the invention is simple and reasonable, and large-scale production can be carried out by utilizing existing industrial equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an aluminum alloy material, and in particular to a method for preparing a high-modulus, high-strength, high-toughness layered microstructure aluminum-based composite material, belonging to the technical field of aluminum alloy materials. Background Art

[0002] Aluminum alloy is one of the main structural materials for aviation, but its modulus is difficult to break through. Material composite is an effective way to improve comprehensive mechanical properties. Adding ceramic particles to aluminum alloy can significantly improve the elastic modulus and strength of aluminum alloy. However, the presence of hard ceramic particles can easily lead to a decrease in the plasticity of the material. On the one hand, the interface reaction of ceramic particles is difficult to control, and the products of the interface reaction cause the material to be destroyed prematurely, reducing the toughness; on the other hand, the large particle size can easily cause local stress concentration, which can cause the particles to break prematurely and accelerate the fracture process.

[0003] Therefore, the in-situ reaction in the aluminum alloy melt is used to generate ceramic particles, which have the advantages of regular particle morphology, small size, and no interface reaction, so that it has good strength and toughness. However, the fine ceramic particles in the aluminum alloy melt are prone to agglomeration, which is not conducive to further improving the strength and plasticity of the material. In addition, the introduction of ceramic particles will refine the grains, which is not conducive to improving toughness.

[0004] The use of heterogeneous structure design can break through the bottleneck problem of improving material strength and plasticity. For example, a "soft" and "hard" alternating layered heterogeneous structure is formed. The hard structure can improve the strength, and the soft tissue part can improve the plasticity and hinder the crack propagation, thereby improving the fracture toughness. At the same time, back stress will be generated near the interface of the "soft" and "hard" regions, and the deformation of the heterogeneous structure will further help improve the strength and plasticity. At present, the layered structure is mainly prepared by cumulative rolling, but this method will introduce a large number of layered interfaces, and the defects, inclusions, and bonding strength at the interface are difficult to control. The surface quality of the plate is high and the preparation process is complicated. Summary of the invention

[0005] In order to solve the problems that micro-nano ceramic particles are difficult to disperse and strength-toughness is difficult to improve simultaneously, the present invention prepares a layered heterogeneous structure in which an in-situ self-generated particle-reinforced aluminum-based composite material and an aluminum alloy structure are alternately distributed, and a layered microstructure distribution is formed in the process from melt to ingot forming, thereby avoiding the problems existing in the rolling technology, solving the problem that fine particles are easy to agglomerate in aluminum alloys and the problem of reduced plasticity caused by conventional strengthening mechanisms, and achieving simultaneous improvement of elastic modulus, strength and elongation.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: using an in-situ autogenous method to prepare a particle-reinforced aluminum-based composite material melt, and preparing an aluminum alloy melt without adding particles, the aluminum-based composite material melt and the aluminum alloy melt are respectively alternately passed through an atomization system and then directly formed layer by layer, and the resulting composite material ingot has no stratified interface defects, and then the ingot is subjected to hot isostatic pressing, annealing, plastic deformation processing, and heat treatment. The processing objects of the present invention are in-situ autogenous particle-reinforced aluminum-based composite materials and aluminum alloy materials, wherein the alloying elements in the aluminum alloy material and the alloying elements in the particle-reinforced aluminum-based composite material can be the same or different, and specifically include the following steps:

[0007] (1) obtaining a TiB2 particle reinforced aluminum matrix composite material and an aluminum alloy material, wherein the mass fraction of TiB2 particles in the TiB2 particle reinforced aluminum matrix composite material is 3-15%;

[0008] (2) heating the TiB2 particle reinforced aluminum-based composite material and the aluminum alloy material in a crucible to obtain a melt, wherein the melt is kept at a temperature of 700-850° C.;

[0009] (3) the two melts in step (2) are passed through an atomizing system to form molten droplets, which are alternately deposited on a rotating tray to form a layered microstructure aluminum-based composite ingot, wherein the alternating time ratio of the deposition of the aluminum-based composite material and the aluminum alloy is 1 to 3;

[0010] (4) subjecting the aluminum-based composite material ingot to homogenization annealing treatment at a temperature of 250-500° C. for a holding time of 2-12 h, followed by air cooling;

[0011] (5) subjecting the homogenized annealed ingot to hot isostatic pressing to obtain an ingot having a density greater than or equal to 99%, and air cooling;

[0012] (6) The ingot described in step (5) is plastically formed, which can be formed by rolling or extrusion;

[0013] (7) subjecting the material subjected to the extrusion or rolling treatment in step (6) to a solution treatment, wherein the solution treatment includes heating, heat preservation and water quenching steps; and then subjecting the material to a cold working deformation treatment at room temperature, wherein the transfer time interval is less than or equal to 1 hour and the deformation amount is 2% to 20%;

[0014] (8) The aluminum-based composite material after cold working deformation treatment is subjected to double-stage aging treatment or single-stage aging treatment.

[0015] Preferably, in step (1), the TiB2 particle size distribution is 20-2000 nm, and the mass fraction of TiB2 particles is 3%, 6%, or 15%.

[0016] Preferably, in step (2), the weight ratio of the TiB2 particle reinforced aluminum-based composite material to the aluminum alloy material is (1-3):1.

[0017] Preferably, in step (3), the aluminum-based composite material melt and the aluminum alloy melt are controlled by an automatic piston rod to alternately open and close the liquid outlet at the bottom of the crucible, so that the two melts flow out alternately, and then pass through an electromagnetic stirring and ultrasonic atomization system, and are alternately sprayed and deposited layer by layer to form an ingot, and the alternating time interval controls the thickness of each layer of the aluminum alloy or aluminum-based composite material.

[0018] Preferably, in step (4), the annealing temperature is 350° C. for 8 hours.

[0019] Preferably, the hot isostatic pressing treatment in step (5) is: using a metal sheath, a pressure greater than or equal to 100 MPa, a hot pressing temperature of 420-550° C., and a holding time of 2-8 hours.

[0020] Preferably, the extrusion forming method is: the extrusion direction is perpendicular to the deposition height direction, and the ingot is kept at 400-460°C for 2-6 hours before hot extrusion forming.

[0021] Preferably, the rolling forming method is as follows: the rolling surface is perpendicular to the deposition height direction, the ingot is kept at 400-460°C for 2-6h and then hot rolled (Example 1-2 is kept at 400°C for 6h, Example 3 is kept at 460°C for 2h), and the single-pass rolling pressure is 5-20% (Example 1-2 is 20%, Example 3 is 5%); the aluminum-based composite material plate after hot rolling is annealed at a temperature of 300-480°C and a holding time of 1-6h (Example 1 is kept at 300°C for 6h, Example 2 is kept at 480°C for 1h, and Example 3 is kept at 350°C for 4h); cold rolling is performed after air cooling, the plate is rolled to a target thickness, and the deformation of each pass during the cold rolling process is 1-5%; the cold-rolled plate is annealed at a temperature of 200-380°C and a holding time of 0.5-10h.

[0022] Preferably, the solution treatment includes single-stage solution treatment or double-stage solution treatment.

[0023] Preferably, the heating temperature of the single-stage solution treatment is 470-510° C., the holding time is 1-5 h, followed by rapid water quenching, and the transfer time is less than or equal to 15 s.

[0024] Preferably, the heating temperature of the two-stage solution treatment is 470°C for 1 hour and 500°C for 30 minutes.

[0025] Then quickly quench with water, and the transfer time is less than or equal to 15s (Example 3 is 470℃ for 1h and 500℃ for 0.5h).

[0026] Preferably, the double-stage aging treatment is carried out at 120-180°C for 10-60 minutes and then at 100°C for 96-240 hours; the single-stage aging treatment temperature is 60-120°C and the insulation time is 120h-720h.

[0027] The invention provides a method for preparing a high-modulus, high-strength and high-toughness layered microstructured aluminum-based composite material, which improves the elastic modulus and strength of the aluminum alloy material while improving the elongation.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention provides a method for preparing a high-modulus, high-strength, high-toughness layered microstructure aluminum-based composite material. Through the processes of in-situ self-generated aluminum-based composite material and aluminum alloy melt alternately spraying forming, plastic deformation and heat treatment, a layered microstructure with non-uniform ceramic particle distribution and non-uniform grain size distribution can be achieved, and the modulus, strength and fatigue performance of aluminum alloy plates can be improved. The process method is simple and easy to operate, and the material preparation, plastic forming and heat treatment processes involved have industrial production conditions. The fine-grained layer of the ceramic particle-reinforced aluminum-based composite material in the present invention can significantly improve the elastic modulus and strength of the aluminum alloy, while the coarse-grained layer of the aluminum alloy can improve the dislocation accommodation capacity, reduce the stress concentration in the fine-grained area, thereby improving the plasticity, thereby improving the overall plasticity of the material; the ceramic particles can not only improve the strength, but also inhibit the cracking of the local slip band of the coarse-grained layer, promote the uniformity of plastic deformation, and improve the plasticity; at the same time, a strain gradient will be formed between the coarse-grained area and the fine-grained area, resulting in strain gradient strengthening. Finally, the effect of simultaneously improving the modulus strength and plasticity can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram of a device for preparing a high modulus, high strength and high toughness layered microstructure aluminum-based composite material;

[0031] Figure 2 Schematic diagram of the microstructure of a high modulus, high strength and high toughness layered microstructure aluminum-based composite material. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0033] Example 1

[0034] This embodiment relates to a method for preparing a high-modulus, high-strength, high-toughness layered microstructure aluminum-based composite material, comprising the following steps:

[0035] (1) First, a mixed salt of NaBF4 and Na2TiF7 with a mass ratio of 2:1 was used to react in aluminum melt at 850°C to generate TiB2 particles, which were then mechanically stirred and ultrasonically treated for 45 min at a stirring speed of 250 rpm and an ultrasonic intensity of 2000 W / m 2 , to achieve uniform TiB2 particles in the aluminum melt, with a size distribution range of 20-2000nm, and finally prepare an Al-4.5Cu-1.8Mg-0.7Mn-0.1Zr (mass fraction, %) aluminum-based composite melt containing 15% TiB2 particles by mass according to the alloy element ratio. At the same time, prepare an Al-4.5Cu-1.8Mg-0.7Mn-0.1Zr (mass fraction, %) aluminum alloy melt without adding particles. The two materials are each refined and degassed before being cast into ingots.

[0036] (2) The aluminum-based composite material ingot and the aluminum alloy ingot of the same weight are placed in the crucible of the spray deposition system for heating. The melt insulation temperature is 850°C, and the auxiliary electromagnetic field system is used for stirring.

[0037] (3) See Figure 1 , through the control of the automatic control system, the piston rod is used to open the bottom switch of the aluminum alloy crucible to make the melt flow out, and after passing through the heating system, electromagnetic stirring system and ultrasonic atomization system, molten droplets are formed, and the melt is deposited on the rotating disk. After the aluminum alloy is deposited for 1 minute, the melt outlet at the bottom of the crucible is closed, and the bottom switch of the aluminum-based composite material crucible is opened at the same time, so that the aluminum-based composite material passes through the heating system, electromagnetic stirring system and ultrasonic atomization system to form molten droplets and deposit on the surface of the aluminum alloy deposited in the previous step, and the deposition time is 2 minutes. The deposition time ratio of the aluminum-based composite material and the aluminum alloy is 2, and the deposition is repeated alternately to obtain a layered microstructure aluminum-based composite material ingot, the ingot diameter is 480mm, and the height is 800mm.

[0038] (4) The aluminum-based composite material ingot obtained by deposition is subjected to homogenization annealing treatment at a homogenization annealing temperature of 500° C. for 2 h, followed by air cooling.

[0039] (5) The ingot after homogenization annealing is subjected to hot isostatic pressing treatment, with pure aluminum jacket, pressure of 100 MPa, temperature of 550°C, holding time of 2 h, and density of 99.2%. After air cooling, the ingot is sawn and milled in a manner that the cross section is perpendicular to the radial direction of the ingot and the thickness is the height direction to prepare the rolling billet. After milling, the billet width is 360 mm and the billet height is 300 mm.

[0040] (6) The aluminum-based composite material ingot after milling is rolled, with the rolling surface perpendicular to the deposition height direction. Before rolling begins, it is kept at 400°C for 6 hours, with a single-pass rolling reduction of 20%, and rolled to 6 mm; the 6 mm thick aluminum-based composite material plate is annealed, kept at 300°C for 6 hours, air-cooled, and cold-rolled to a thickness of ~2.5 mm, with a reduction of 5% per pass, and then the cold-rolled plate is annealed at 200°C for 10 hours.

[0041] (7) The cold-rolled sheet was then subjected to a single-stage solution treatment process, wherein the solution treatment process was 510°C for 1 h, followed by rapid water quenching, with a transfer time of less than 10 s; the sheet was transferred to a rolling mill within 30 min and cold-rolled at room temperature to a thickness of 2 mm with a thickness deformation of 20%.

[0042] (8) Finally, the plate was subjected to a double-stage aging treatment with the process parameters of 180°C for 10 minutes and then 100°C for 240 hours.

[0043] The microstructure of the obtained TiB2 particle reinforced Al-4.5Cu-1.8Mg-0.7Mn-0.1Zr aluminum matrix composite sheet is shown in Figure 2 As shown, the aluminum alloy structure and the TiB2 particle reinforced aluminum matrix composite structure are alternately distributed in the height direction of the ingot, and the alloy structure has a large grain size, while the composite material area has a small grain size. The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of the TiB2 particle reinforced Al-4.5Cu-1.8Mg-0.7Mn-0.1Zr aluminum matrix composite sheet is 80GPa, the yield strength is 480MPa, the tensile strength is 610MPa, and the elongation is 18%.

[0044] Example 2

[0045] This embodiment relates to a method for preparing a high-modulus, high-strength, high-toughness layered microstructure aluminum-based composite material, which is basically the same as the method in Example 1, except that the weight ratio of the aluminum-based composite material to the aluminum alloy is 3, the deposition time of the aluminum-based composite material in the ingot deposition preparation process is 6 minutes, and the aluminum alloy material is deposited for 2 minutes. In the plastic forming step, the hot-rolled aluminum-based composite material plate is annealed at 480°C for 1 hour; the cold-rolled plate is annealed at 380°C for 0.5 hours. After solution treatment, the cold-rolled plate is cold-rolled and deformed by 10%, rolled by 2.25 mm, and then subjected to single-stage aging treatment, with an aging temperature of 120°C for 720 hours.

[0046] The room temperature mechanical property test along the rolling direction shows that the elastic modulus of the aged aluminum-based composite material plate is 84 GPa, the yield strength is 500 MPa, the tensile strength is 620 MPa, and the elongation is 16%.

[0047] Example 3

[0048] This embodiment relates to a method for preparing a high modulus, high strength and high toughness layered microstructure aluminum-based composite material, comprising the following steps:

[0049] (1) First, a 3wt.% TiB2 particle-reinforced Al-4.5Cu-1.8Mg-0.7Mn-0.1Zr (mass fraction, %) aluminum-based composite melt was prepared in situ by a mixed salt method of KFB4 and K2TiF6, wherein the TiB2 particle size distribution was 20-2000nm; and an Al-6.5Zn-2.0Mg-2.0Cu-0.1Zr (mass fraction, %) aluminum alloy melt without adding particles was prepared; and the two materials were each refined and degassed before being cast into ingots.

[0050] (2) The aluminum-based composite material ingot and the aluminum alloy ingot of the same weight are placed in the crucible of the spray deposition system for heating. The melt insulation temperature is 750°C, and the electromagnetic field system is used for stirring.

[0051] (3) Then, by controlling the automatic control system, the switch at the bottom of the aluminum alloy crucible is turned on to allow the melt to flow out, and after passing through the atomization system, molten droplets are formed, and the melt is deposited on the rotating disk. After the aluminum alloy is deposited for 2 minutes, the melt outlet at the bottom of the crucible is closed, and at the same time, the switch at the bottom of the aluminum-based composite material crucible is turned on to allow the aluminum-based composite material to pass through the atomization system to form molten droplets and deposit on the surface of the aluminum alloy deposited in the previous step. The deposition time is 2 minutes. By performing this reciprocating alternating deposition, a layered microstructure aluminum-based composite material ingot can be obtained, and the ingot diameter is 480 mm and the height is 800 mm.

[0052] (4) The deposited aluminum-based composite ingot is then subjected to homogenization annealing treatment at a temperature of 350° C. for 8 h, followed by air cooling.

[0053] (5) The ingot after homogenization annealing is subjected to hot isostatic pressing treatment, using pure aluminum sheathing, with a pressure of 200 MPa, a temperature of 420°C, a holding time of 8 h, and a density of 99.2%; after air cooling, the ingot is sawn and milled in a manner such that the cross section is perpendicular to the radial direction of the ingot and the thickness is in the height direction to prepare a rolled billet. After milling, the billet width is 360 mm and the billet height is 300 mm.

[0054] (6) The aluminum-based composite ingot after milling is hot rolled, with the rolling surface perpendicular to the deposition height direction, and is kept at 460°C for 2 hours before rolling begins. The reduction amount of a single rolling pass is 5%, and the rolling is carried out to 10 mm. The 10 mm thick aluminum-based composite plate is annealed, kept at 350°C for 4 hours, and then cold rolled to a thickness of 4.5 mm after air cooling. The reduction amount of each pass is 1%, and then the cold-rolled plate is annealed at 250°C and the insulation time is 6 hours.

[0055] (7) The cold-rolled sheet was then subjected to a two-stage solution treatment process, wherein the solution treatment process was 470°C for 1 h and 500°C for 0.5 h, followed by rapid water quenching with a transfer time of less than 15 s; the sheet was transferred to a rolling mill within 30 min and cold rolled at room temperature to a thickness of 4 mm with a thickness deformation of ~10%.

[0056] (8) Finally, the plate after solid solution was subjected to a double-stage aging treatment, with the process parameters of 120°C for 60 min and then 100°C for 96 h.

[0057] The room temperature mechanical property test along the rolling direction showed that the elastic modulus of the TiB2 particle reinforced aluminum matrix composite material plate was 75 GPa, the yield strength was 740 MPa, the tensile strength was 800 MPa, and the elongation was 15%.

[0058] Example 4

[0059] This embodiment relates to a method for preparing a high-modulus, high-strength, high-toughness layered microstructure aluminum-based composite material, comprising the following steps:

[0060] (1) First, a 6wt.% TiB2 particle-reinforced Al-6.5Zn-2.2Mg-2.2Cu-0.1Zr (mass fraction, %) aluminum matrix composite material melt was prepared in situ by a mixed salt method of NaFB4 and Na2TiF6, wherein the TiB2 particle size distribution was 20-2000nm, and an Al-6.5Zn-2.2Mg-2.2Cu-0.1Zr (mass fraction, %) aluminum alloy melt without adding particles was prepared. Both materials were refined and degassed and then cast into ingots.

[0061] (2) The aluminum-based composite material ingot and the aluminum alloy ingot of the same weight are placed in the crucible of the spray deposition system for heating. The melt insulation temperature is 700°C, and the auxiliary electromagnetic field system is used for stirring.

[0062] (3) Then, by controlling the automatic control system, the switch at the bottom of the aluminum alloy crucible is turned on to allow the melt to flow out, and after passing through the atomization system, molten droplets are formed, and the melt is deposited on the rotating disk. After the aluminum alloy is deposited for 2 minutes, the melt outlet at the bottom of the crucible is closed, and at the same time, the switch at the bottom of the aluminum-based composite material crucible is turned on to allow the aluminum-based composite material to pass through the atomization system to form molten droplets and deposit on the surface of the aluminum alloy deposited in the previous step. The deposition time is 3 minutes. By performing this reciprocating deposition alternately, a layered microstructure aluminum-based composite material ingot can be obtained, and the ingot diameter is 480 mm and the height is 800 mm.

[0063] (4) The deposited aluminum-based composite ingot is then subjected to homogenization annealing treatment at a temperature of 250° C. for 12 h and then air-cooled.

[0064] (5) subjecting the homogenized annealed ingot to hot isostatic pressing, using a pure aluminum jacket, a pressure of 200 MPa, a temperature of 450° C., a holding time of 8 h, and a density of 99.2%; after air cooling, milling along the radial direction of the ingot into an extrusion prefabricated ingot with a diameter of 250 mm;

[0065] (6) The ingot was kept at 400°C for 6 h and then extruded into a rod with a diameter of 15 mm.

[0066] (7) The extruded rod is then subjected to a single-stage solution treatment, wherein the solution treatment process is to maintain the temperature at 470°C for 5 hours, followed by rapid water quenching, with a transfer time of less than 10 seconds; after water quenching, the rod is stretched at room temperature, with a transfer time of less than 60 minutes and a deformation of 2%.

[0067] (8) Finally, the extruded rod is subjected to a single-stage aging treatment with the process parameters of 60°C for 240 h.

[0068] The room temperature mechanical property test along the extrusion direction showed that the elastic modulus of the aluminum-based composite material rod after aging was 77Gpa, the yield strength was 740Mpa, the tensile strength was 800Mpa, and the elongation was 14%.

[0069] Example 5

[0070] This embodiment relates to a method for preparing a high-modulus, high-strength, high-toughness layered microstructure aluminum-based composite material, which is basically the same as the method in Example 4, except that: during the preparation of the ingot, the aluminum-based composite material is deposited for 6 minutes, and the aluminum alloy material is deposited for 2 minutes, and the ingot is formed by alternating deposition. In the plastic forming step, the ingot is kept at 460°C for 2 hours and then extruded. Finally, the bar is subjected to a single-stage aging treatment process parameter of 80°C for 120 hours.

[0071] The room temperature mechanical properties test along the extrusion direction showed that the elastic modulus of the Al-6.5Zn-2.2Mg-2.2Cu-0.1Zr composite material was 79 GPa, the yield strength was 760 MPa, the tensile strength was 810 MPa, and the elongation was 12%.

[0072] Comparative Example 1

[0073] The implementation steps of this comparative example are basically the same as those of Example 1, except that the alternating deposition time of the aluminum alloy and the aluminum-based composite material is different during the preparation of the ingot, wherein the aluminum alloy is deposited for 2 minutes and the aluminum-based composite material is deposited for 1 minute.

[0074] The room temperature mechanical property test along the rolling direction shows that the elastic modulus of the Al-4.5Cu-1.8Mg-0.7Mn-0.1Zr aluminum-based composite material plate is 78GPa, the yield strength is 400MPa, the tensile strength is 530MPa, and the elongation is 15%. The elastic modulus, strength and elongation of the comparative example material are all lower than those of Example 1.

[0075] Comparative Example 2

[0076] The implementation steps of this comparative example are basically the same as those of Example 1, except that only one material, aluminum alloy, is deposited during the ingot preparation process.

[0077] The room temperature mechanical property test along the rolling direction shows that the elastic modulus of the aged aluminum alloy plate is 72GPa, the yield strength is 360MPa, the tensile strength is 550MPa, and the elongation is 16%. The modulus, strength and plasticity of the comparative example material are all lower than those of Example 1.

[0078] Comparative Example 3

[0079] The implementation steps of this comparative example are basically the same as those of Example 2, except that the obtained aluminum-based composite material plate is subjected to conventional aging treatment, the cold-rolled plate is not annealed before solution treatment, and the aging treatment parameters are 180° C. for 20 h.

[0080] The room temperature mechanical property test along the rolling direction shows that the elastic modulus of the aluminum-based composite material plate after aging is 84GPa, the yield strength is 380MPa, the tensile strength is 520MPa, and the elongation is 12%. The elastic modulus of the comparative material is the same as that of the material in Example 2, but the strength and elongation of the comparative material are significantly lower than those in Example 2.

[0081] Comparative Example 4

[0082] The implementation steps of this comparative example are basically the same as those of Example 4, except that the alternating deposition time of the aluminum alloy and the aluminum-based composite material is different during the preparation of the ingot, wherein the aluminum alloy is deposited for 3 minutes and the aluminum-based composite material is deposited for 2 minutes.

[0083] The room temperature mechanical property test along the extrusion direction shows that the elastic modulus of the aluminum-based composite material bar after aging is 74GPa, the yield strength is 660MPa, the tensile strength is 700MPa, and the elongation is 10%. The elastic modulus, strength and elongation of the comparative example material are lower than those of Example 4.

[0084] Comparative Example 5

[0085] The implementation steps of this comparative example are basically the same as those of Example 4, except that only one material, aluminum alloy, is deposited during the ingot preparation process.

[0086] The room temperature mechanical property test along the extrusion direction shows that the elastic modulus of the aluminum-based composite material bar after aging is 72GPa, the yield strength is 620MPa, the tensile strength is 680MPa, and the elongation is 12%. The strength, plasticity and elastic modulus of the comparative example material are lower than those of Example 4.

[0087] Comparative Example 6

[0088] The implementation steps of this comparative example are basically the same as those of Example 5, except that the alternating deposition time of the aluminum alloy and the aluminum-based composite material is different during the preparation of the ingot, wherein the aluminum is deposited for 6 minutes and the aluminum-based composite material is deposited for 2 minutes.

[0089] The room temperature mechanical property test along the extrusion direction shows that the elastic modulus of the aluminum-based composite material bar after aging is 74GPa, the yield strength is 660MPa, the tensile strength is 700MPa, and the elongation is 9%. The elastic modulus, strength and elongation of the comparative example material are significantly lower than those of Example 5.

[0090] Comparative Example 8

[0091] The implementation steps of this comparative example are basically the same as those of Example 3, except that the two materials used do not contain TiB2 ceramic particles, and the final plate is subjected to conventional aging treatment and is kept at 180°C for 20 hours.

[0092] The room temperature mechanical property test along the rolling direction shows that the elastic modulus of the aluminum-based composite material plate is 72 GPa, the yield strength is 480 MPa, the tensile strength is 570 MPa, and the elongation is 10%. The strength and elongation of the comparative example material are lower than those of Example 3.

[0093] The method described in the present application can be applied to the preparation of composite materials with different alloy components. By alternately depositing and compounding two materials, combined with specific annealing treatment, cold working deformation treatment and aging treatment processes, the elastic modulus, yield strength, tensile strength and elongation can be improved at the same time.

[0094] The above describes the specific embodiments of the present invention. By comparing the embodiments with the comparative examples, the method of the present invention provides a method for preparing a high modulus, high strength and high toughness layered microstructure aluminum-based composite material, which can simultaneously improve the elastic modulus, tensile strength and elongation of the aluminum alloy.

[0095] It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments may be combined with each other at will.

Claims

1. A method for preparing a high modulus, high strength and high toughness layered microstructure aluminum-based composite material, characterized in that: The following steps are involved: (1) obtaining a TiB2 particle reinforced aluminum matrix composite material and an aluminum alloy material, wherein the mass fraction of TiB2 particles in the TiB2 particle reinforced aluminum matrix composite material is 3-15%; (2) heating the TiB2 particle reinforced aluminum-based composite material and the aluminum alloy material in a crucible to obtain a melt, wherein the melt is kept at a temperature of 700-850° C.; (3) the two melts in step (2) are passed through an atomizing system to form molten droplets, which are alternately deposited on a rotating tray to form a layered microstructure aluminum-based composite ingot, wherein the alternating time ratio of the deposition of the aluminum-based composite material and the aluminum alloy is 1 to 3; (4) subjecting the aluminum-based composite material ingot to homogenization annealing treatment at a temperature of 250-500° C. for a holding time of 2-12 h, followed by air cooling; (5) subjecting the homogenized annealed ingot to hot isostatic pressing to obtain an ingot having a density greater than or equal to 99%, and air cooling; (6) the ingot described in step (5) is subjected to plastic forming, wherein the plastic forming includes rolling or extrusion forming; (7) subjecting the material subjected to the extrusion or rolling treatment in step (6) to a solution treatment, wherein the solution treatment includes heating, heat preservation and water quenching steps; and then subjecting the material to a cold working deformation treatment at room temperature, wherein the transfer time interval is less than or equal to 1 hour and the deformation amount is 2% to 20%; (8) The aluminum-based composite material after cold working deformation treatment is subjected to double-stage aging treatment or single-stage aging treatment.

2. The method according to claim 1, characterized in that In the step (1), the TiB2 particle size distribution is 20-2000 nm, and the mass fraction of TiB2 particles is 3%, 6%, or 15%.

3. The method according to claim 1, characterized in that In the step (2), the weight ratio of the TiB2 particle reinforced aluminum-based composite material to the aluminum alloy material is (1-3):

1.

4. The method according to claim 1, characterized in that In the step (4), the annealing temperature is 350° C. for 8 hours.

5. The method according to claim 1, characterized in that The hot isostatic pressing treatment in step (5) is as follows: using a metal sheath, the pressure is greater than or equal to 100 MPa, the hot pressing temperature is 420-550° C., and the holding time is 2-8 hours.

6. The method according to claim 1, characterized in that In the step (6), the extrusion forming method is: the extrusion direction is perpendicular to the deposition height direction, and the ingot is kept at 400-460°C for 2-6 hours and then hot extrusion is performed.

7. The method according to claim 1, characterized in that In the step (6), the rolling forming method is as follows: the rolling surface is perpendicular to the deposition height direction, the ingot is kept at 400-460°C for 2-6 hours and then hot rolled, and the single-pass rolling reduction is 5-20%; the aluminum-based composite material plate after hot rolling is annealed at a temperature of 300-480°C and a holding time of 1-6 hours; after air cooling, cold rolling is performed, the plate is rolled to a target thickness, and the deformation of each pass during the cold rolling process is 1-5%; the cold rolled plate is annealed at a temperature of 200-380°C and a holding time of 0.5-10 hours.

8. The method according to claim 1, characterized in that The solution treatment includes single-stage solution treatment or double-stage solution treatment. The heating temperature of the single-stage solution treatment is 470-510°C, the holding time is 1-5h, followed by rapid water quenching, and the transfer time is less than or equal to 15s; the heating temperature of the double-stage solution treatment is 470°C for 1h and 500°C for 30min, followed by rapid water quenching, and the transfer time is less than or equal to 15s.

9. The method according to claim 1, characterized in that The double-stage aging treatment is carried out by keeping the temperature at 120-180° C. for 10-60 minutes and then keeping the temperature at 100° C. for 96-240 hours; the single-stage aging treatment temperature is 60-120° C. and the holding time is 120 hours to 720 hours.

Citation Information

Patent Citations

  • Manufacturing method for aluminum matrix composite-aluminum alloy sandwich panel

    CN105458263A

  • Strengthening and toughening heat treatment method of in-situ titanium boride particle reinforced aluminum matrix composite

    CN108611583A

  • Preparing method for aluminum-based nano composite material

    CN108746625A

  • Dispersion-strengthened high-silicon aluminum alloy and preparation method thereof

    CN112746200A

  • Carbon fiber reinforced aluminum-silicon-based composite material and preparation method thereof

    CN112813364A